Lots more tell me why: answers to hundreds of questions children ask. - Leokum, Arkady; Koehler, Cynthia Iliff; Koehler, Alvin (New York, Reed Childrens, 1972)
Questions and answers about such things as the world around us and how it began, the human body, how other creatures live, and how things are made.
Keywords: Children's questions and answers; Questions and answers